HISTORY OF EMERGENCE AND DEVELOPMENT OF ECOLOGICAL BUILDINGS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article discusses the historical development of urban planning and the design of cities with ideal living environments. The article highlights efforts to improve the living environment, including architectural works, sewage technologies, and sanitary-hygienic measures. Overall, the article provides a historical perspective on the evolution of urban planning and highlights the importance of considering social and environmental aspects in urban design..